2022
DOI: 10.1039/d2fo00936f
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-inflammatory and antibiofilm activities of bacterial lysates from lactobacilli against oral pathogenic bacteria

Abstract: Postbiotics are functional biological compounds, such as bacterial lysates (BLs) released from probiotic bacteria. Although postbiotics exert various bioactivities, the anti-inflammatory and antibiofilm activities of BLs against oral pathogenic bacteria...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A similar result was observed in a study where the biosurfactant produced by the analyzed postbiotic significantly decreased the gene expression of gtfB and gtfC in S. mutans biofilms [35]. Similarly, bacterial lysates (BLs), another type of postbiotic, of Lactobacillus plantarum and L. rhamnosus GG downregulated gtf B, gtf C, and gtf D by S. mutans, suggesting that BLs reduce the synthesis of extracellular polysaccharide and thereby reduce S. mutans biofilm, but did not eradicate the established S. mutans biofilm [36].…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was observed in a study where the biosurfactant produced by the analyzed postbiotic significantly decreased the gene expression of gtfB and gtfC in S. mutans biofilms [35]. Similarly, bacterial lysates (BLs), another type of postbiotic, of Lactobacillus plantarum and L. rhamnosus GG downregulated gtf B, gtf C, and gtf D by S. mutans, suggesting that BLs reduce the synthesis of extracellular polysaccharide and thereby reduce S. mutans biofilm, but did not eradicate the established S. mutans biofilm [36].…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of various cytokines, including IL-6, has been associated with the PI3K/Akt signaling pathway [ 26 ]. Additionally, studies have reported that MAPKs and NF-κB signaling pathways play essential roles in cytokine and chemokine production [ 24 ]. IκBs, such as IκBα, play a crucial role in localizing NF-κB in the cytosol, therefore preventing its transcriptional activity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, L. heleveticus LH2171 attenuated the expression of IL-6 and IL-8 in gingival epithelial cells stimulated by P. gingivalis [ 23 ]. A recent study also demonstrated that bacterial lysates from L. plantarum and L. rhamnosus GG inhibited IL-1β, IL-6, and MCP-1 production induced by P. gingivalis LPS [ 24 ]. Postbiotics, specifically probiotic cell wall-associated components, have emerged as promising molecules that exhibit beneficial effects typically attributed to probiotics [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…L. plantarum ATCC 14917 was obtained from the American Type Cell Culture (ATCC; Manassas, VA, USA) and cultured as described previously ( Kim et al, 2022 ). Genomic DNA of L. plantarum (LpDNA) was extracted using a Wizard Genomic DNA Purification Kit (Promega, Madison, WI, USA) following the manufacturer’s instructions with slight modifications.…”
Section: Methodsmentioning
confidence: 99%